Targeting Chromosome 21 Gene Over-Expression: A Novel Approach to Prevent Health Complications in Individuals with Down Syndrome. - Zardari, Shehnila; Shar, Nisar Ahmed; Chohan, Afshan; Majeed, Ayesha (International Journal of Endorsing Health Science Research, 2024)
Background: Down Syndrome (DS), caused by an extra copy of chromosome 21, leads to over-expression of 200–300 genes. This genetic imbalance contributes to various health complications, including an elevated risk of blood cancers. Modulating gene expression is vital to mitigating these risks. Methodology: This study focused on reducing the over-expression of genes on chromosome 21 by inhibiting the proteins they encode. Potential inhibitors were identified and evaluated using electrostatic interaction scoring and protein docking simulations. The goal was to reduce gene expression by 50%, thereby mitigating the harmful effects of over-expressed proteins. Results: Analysis confirmed significantly higher expression levels of chromosome 21 genes in DS individuals. Targeting the encoded proteins successfully reduced gene expression by 50%. Protein docking studies identified a promising inhibitor that effectively blocked over-expressed proteins, demonstrating potential to prevent blood cancer by mitigating the effects of the extra genetic material. Conclusion: This study proposes a novel therapeutic strategy for DS by focusing on inhibiting the over-expressed proteins linked to blood cancer. The identified drug candidates hold promise for improving health outcomes and quality of life in individuals with DS by reducing the risk of blood cancers and other complications.